Simple science experiments with water - Orii, Eiji, 1909-; Orii, Masako; Fujishima, Kaoru (Milwaukee, WI : Gareth Stevens, 1989)
Presents experiments demonstrating the buoyancy of water.
Includes index.
Booklist.
4.8
3-6
Keywords: Archimedes' principle -- Experiments -- Juvenile literature; Archimedes' principle -- Experiments; Floating bodies -- Experiments; Water -- Experiments; Experiments; Archimedes' principle -- Experiments; Floating bodies -- Experiments; Water -- Experiments; Archimedes' principle -- Experiments; Floating bodies -- Experiments; Water -- Experiments